1980
DOI: 10.1093/schbul/6.4.579
|View full text |Cite
|
Sign up to set email alerts
|

Course of Schizoaffective Psychoses: Results of a Followup Study

Abstract: The course of illness was investigated retrospectively and prospectively in a sample of 150 hospitalized schizoaffective patients and 95 hospitalized bipolar manic-depressive patients. The two disorders showed more similarities than differences in their course; this was true for the age of onset (31.8 versus 34.7 years) and the length of illness until the end of the observation period (22.5 versus 23.8 years). Schizoaffective disorders took a more benign course than bipolar disorders, as measured by the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…This finding is in accordance with data regarding the affective nature of SAD episodes, e.g. Angst et al [14] found that 64% of the patients had manic or mixed manic and depressive symptomatology. In our study, only 17% of the patients had pure depressive episodes.…”
Section: Sad Subtypessupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in accordance with data regarding the affective nature of SAD episodes, e.g. Angst et al [14] found that 64% of the patients had manic or mixed manic and depressive symptomatology. In our study, only 17% of the patients had pure depressive episodes.…”
Section: Sad Subtypessupporting
confidence: 92%
“…Angst et al [14] found that SAD and bipolar disorder had more similarities than differences in their course, and that SAD had a somewhat more benign course than bipolar disorder, while others showed that SAD has a worse course and outcome than bipolar disorder [5,9] . Findings regarding the impact of SAD subtype on the course and prognosis are inconsistent as well, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This appears to have face validity in terms of patients reporting ‘self‐medication’ of depressive or manic symptoms by illicit substances. Third, higher numbers of manic and depressive episodes are associated with a shortening of the cycle and increased rate of relapse . Fourth, untreated illness may interfere with the attainment of age‐specific social, psychological, and educational developmental goals.…”
Section: Is Early Intervention Justified In Bd?mentioning
confidence: 99%
“…The problem with the concept of 'schizoaffective' as a solution to the problem of demarcation between schizophrenia and affective psychosis is the heterogenousnature of the syndromeevenwhenoperationally defined. Follow-up studies indicate that while, as a group, the prognosisof schizoaffectives liessomewhere between schizophrenia and affective disorders, there is considerable variability in outcome, with some subgroups resembling schizophrenia and others closer to affectivedisorder (Tsuang & Dempsey, 1979;Angst et al, 1980;Brockington et al, 1980a, b;Pope et al, 1980;Grossman et al, 1984;Maj, 1985;Levinson & Levitt, 1987;Williams & McGlashen, 1987). Schneider's (1959), approach to the problem of demarcation was to suggest that there were certain first rank symptoms (FRS) which were pathognomonic for schizophrenia.…”
Section: The Problem Of Demarcationmentioning
confidence: 99%